SIMULIUM LANEPORTOI N N SIMULIIDAE DIPT Y LISTA DE SIMULIDOS MEXICANOS - VARGAS, LUIS (My University, 1942)
Originally described by Roubaud (1906) as subgenus, the great majority of authors following to Edwards (1931) accord to Eusimulium the same rank E pilosum therefore must be considered as S (E) pilosum (Knowlton and Rowe, 1934); then as S pillosum Lan
REV INST SALUBR ENFERM TROP
Keywords: SIMULIUM, LANEPORTOI, LISTA, SIMULIDOS, MEXICANOS; CIENCIAS MEDICAS; SALUD PUBLICA